Managing Risk in Communication Encounters : Strategies for the Workplace. - Waldron, Dr. Vincent R. (SAGE Publications, 2010)
This book focuses on the types of risky interactions that threaten identities, relationships, and sometimes careers, including voicing dissent, repairing broken relationships, managing privacy, responding to harassment, offering criticism, and communicating emotion. Each chapter is grounded in real-life organizational scenarios, includes recent research, applies a standard theoretical framework, and illustrates a full range of communicative tactics and discourse practices. Throughout the book, authors Vincent R. Waldron and Jeffrey W. Kassing provide examples to spur thinking, raise questions.